Polarons induced electronic transport, dielectric relaxation and magnetodielectric coupling in spin frustrated Ba2FeWO6. (April 2016) - Pezhumkattil Palakkal, Jasnamol; Lekshmi, P. Neenu; Thomas, Senoy; Valant, Matjaz; Suresh, K.G.; Varma, Manoj Raama
Graphical abstract: Highlights: Ordered double perovskite Ba2 FeWO6 synthesized in reducing atmosphere possess a tetragonal I4/m crystal structure with mixed valent Fe/W cations. Ba2 FeWO6 has an antiferromagnetic structure with T N at 19 K. Insulating Ba2 FeWO6 shows different conducting mechanisms at different temperature regions and dielectric relaxation. The polarons invoked by the mixed valence state of cations and their disordered arrangements are solely responsible for the various physical phenomena observed in Ba2 FeWO6 . Abstract: Mixed valent double perovskite Ba2 FeWO6, with tetragonal crystal structure, synthesized in a highly controlled reducing atmosphere, shows antiferromagnetic transition at T N  = 19 K. A cluster glass-like transition is observed around 30 K arising from the competing interactions between inhomogeneous magnetic states. The structural distortion leads to the formation of polarons that are not contributing to DC conduction below charge ordering temperature, T CO  = 279 K. Above T CO, small polarons will start to hop by exploiting thermal energy and participate in the conduction mechanism. The polarons are also responsible for the dielectric relaxor behavior, in which the dielectric relaxation time follows non-linearity in temperature as proposed by Fulcher. The material also exhibits a small room temperature magnetoresistance of 1.7% at 90 kOe. An intrinsic magnetodielectric coupling of ∼4% near room temperature and at lower temperatures, as well as an extrinsic magnetodielectric coupling change from +4% to −6% at around 210 K are reported.